APLIKASI METODE AMBANG BERTINGKAT UNTUK ANALISIS POTENSI BANJIR: STUDI PENDAHULUAN PADA 15 DAS DI JAWA TIMUR - Indarto Indarto; Sri Wahyuningsih; Muhardjo Pudjojono; Hamid Ahmad; Tino Bachtiar (Faculty of Agricultural Technology, University of Jember, 2015)
This research deals with identification of potential flood discharge from 15 watersheds located in Eastern Part of East Java Province. Recorded times series of daily discharges data are used as main input for the analysis. The discharge data for each watershed are rangked from lowest to high value. Then, the value of discharge correspond to quantile 90% (Q90) is calculated and determined as the threshold level for each watershed. In this case, discharge data more than > Q90 value is categorized as flood events. Then, the frequency of flood events are calculated based on monthly or annual time interval. Furthermore, spatial distribution of flood events are visualized by comparing the frekuency of flood events amongs the watersheds. Finally, thematics maps corresponde to waterheds properties, frequency of flood events, and rainfall event are presented.Keywords: Threslod level method, waterheds, flood indice, East Java